Examining university students’ perceptions on stigma surrounding students with intellectual disabilities in Saudi Arabia - Alkeraida, Ali (Frontiers in Education, 2025)
BackgroundThe persistent stigma surrounding students with intellectual disabilities, particularly exhibited by students without disabilities, continues to pose a barrier to fostering participation. Thus, many university students with visible or invisible disabilities have expressed a preference not to be identified as having a disability. Limited efforts to address this issue at the university level in this regard. Therefore, this study aimed to explore the differences across demographic variables that may influence university students’ perceptions on stigma related to students with intellectual disabilities.MethodThe study employed a quantitative descriptive design, using the Goratu Questionnaire as the primary instrument to explore the phenomenon. Data were collected using simple random sampling, comprising of 159 university students in Saudi Arabia.ResultsThe analysis considered several variables, including sex, level of education, contact with individuals with disabilities, and academic major. The study results not only reveal significant differences in students’ perceptions based on their sex and level of education but also indicate that female students expressed significantly less stigma than did male students while undergraduate students demonstrated more stigma than did postgraduates.ConclusionThe findings of the study highlight the need to implement anti-stigma interventions and systematically measure their impact. Future research may benefit from adopting a longitudinal approach to track changes in perceptions over time.